Malicious URL Detection using Machine Learning - Prenalee Nanaware (International Journal of Integrated Science and Technology, 2024)
One of the most prevalent and least protected security risks in existence today is fraudulent websites and URLs.We offer a method that both uses machine learning characteristics to identify phishing URLs and employs text processing techniques to evaluate text and identify incorrect remarks that are suggestive of phishing assaults.